2020
DOI: 10.2147/ndt.s272278
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association Between Glutathione Peroxidase-1 (GPx-1) Polymorphisms and Schizophrenia in the Chinese Han Population</p>

Abstract: The dopamine and oxidative stress hypotheses are leading theories of the pathoetiology of schizophrenia (SCZ). Glutathione Peroxidase 1 (GPx-1), a major antioxidant enzyme, and the most abundantly expressed member of the GPx family, plays an important role in metabolic dopamine changes, which are closely related to neurological and psychiatric disorders. The impact of GPx-1 polymorphisms has rarely been explored in the field of SCZ. Here, we explored the possible relationship between GPx-1 gene polymorphisms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Overall, there is considerable evidence that GPx1 polymorphisms have a strong association with some diseases (Buraczynska et al, 2017 ; Hong et al, 2013 ; Jerotic et al, 2019 ; Souiden et al, 2016 ; Wei et al, 2020 ). In particular, the polymorphic site containing the alanine stretch has been found to be related with cancer (Jefferies et al, 2005 ; Kote‐Jarai et al, 2002 ), cardiovascular diseases (Hamanishi et al, 2004 ), and mental disorders such as schizophrenia (Shao et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, there is considerable evidence that GPx1 polymorphisms have a strong association with some diseases (Buraczynska et al, 2017 ; Hong et al, 2013 ; Jerotic et al, 2019 ; Souiden et al, 2016 ; Wei et al, 2020 ). In particular, the polymorphic site containing the alanine stretch has been found to be related with cancer (Jefferies et al, 2005 ; Kote‐Jarai et al, 2002 ), cardiovascular diseases (Hamanishi et al, 2004 ), and mental disorders such as schizophrenia (Shao et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, GPx is the key enzyme for ADS in the brain tissue to scavenge excess H 2 O 2 because the CAT activity in the brain is low and is limited to peroxisomes. It has been confirmed that there is a close relationship between decreased GPx activity and the severity of schizophrenia, which may be related to DA metabolism [ 74 , 75 ]. Buckman et al found that brain atrophy was negatively correlated with GPx activity in patients with chronic schizophrenia [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immune system [51], axon guidance [52], metabolism [53], diseases of metabolism [54] and neuronal system [55] were lined with advancement of BD. Altered expression of SLC6A9 [56] and RHD (Rh blood group D antigen) [57], CHRFAM7A [58], ANXA3 [59], SLC1A5 [60], KCNH2 [61], HP (haptoglobin) [62], SELENBP1 [63], SNCA (synuclein alpha) [64], TGM2 [65], PINK1 [66], B2M [67], QPCT (glutaminyl-peptide cyclotransferase) [68], CBS (cystathionine beta-synthase) [69], NQO2 [70], GLRX5 [71], BASP1 [72], GAS7 [73], GPX1 [74], OLIG2 [75], RPTN (repetin) [76], IL33 [77], SOX10 [78], GRIK1 [79], ZFPM2 [80], SHANK3 [81], ERBB3 [82], ARC (activity regulated cytoskeleton associated protein) [83], GFAP (glial fibrillary acidic protein) [84], PLAT (plasminogen activator, tissue type) [85], GRIK5 [86], CACNB2 [87], NRXN2 [88], TERT (telomerase reverse transcriptase) [89], GNB3 [90], L1CAM [91], EGR3 [92], CAV1 [93], CACNA1B [94], MAGI1 [95], KIR2DL1 [96], PAH (phenylalanine hydroxylase) [97] and CYP3A5 [98] have been shown in schizophrenia. Recent studies showed that SLC6A9 [99], FKBP1B [100], S100A12 [101], SLC6A19 [102], TXN (thioredoxin) [103], TLR9 [104], HP (haptoglobin) [105], ARG1 [106], PINK1 [107], B2M [108], C5AR1 [109], MYADM (myeloid associated differentiation marker) [110], CBS (cystathionine beta-synthase) [111], GPX1 [112], SIAH2 [113], PRDX2 [114], RDH8 [115], CYP11B2 [116], RARRES2 [117], NOX1 [118], IL33 [119], OTC (ornithine transcarbamylase) [120], CYP1A1 […”
Section: Discussionmentioning
confidence: 99%